POLA KOMUNIKASI, PENGAMBILAN KEPUTUSAN, DAN KESEJAHTERAAN KELUARGA JARAK JAUH: KASUS PADA KELUARGA MAHASISWA PASCASARJANA - Muladsih, Oktavia Rattika; Muflikhati, Istiqlaliyah; Herawati, Tin (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2011)
This research was to analyze social support, communication patterns, decision making, and family well-being; the correlation among research variables; and variables that influence to communication patterns, decision making, and family well-being of long distance family. This research involved 75 families that were selected by snowball sampling. Data was analyzed by descriptive, Pearson’s correlation, and multiple linear regression. Results showed that families had high social support from nuclear family and moderate social support from big family and friends. Comunication pattern between participants with their couple and child in high category. Comunication pattern correlated significantly with family’s income per capita and contribution of wife’s income. Communication pattern was influenced by social support. Results also indicated that most decision in family was taken together although they are long distance family. Decision making was influenced by amount of family members. Based on objective and subjective family well-being indicator, most family had high level of welfare. Subjective well-being was influenced by social support and communication pattern.